2016
DOI: 10.1097/md.0000000000003948
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cancer-related fatigue outcomes in patients with locally advanced prostate cancer after intensity-modulated radiotherapy combined with hormonal therapy

Abstract: The aim of our study was to investigate the relationship between cancer-related fatigue and clinical parameters, and the effect factors of fatigue for the prostate cancer patients. Long-term follow-up is performed using the Fatigue Symptom Inventory before treatment (A), at the end of intensity-modulated radiotherapy (B), and 3 months (C), 12 months (D), 24 months (E), 36 months (F), and 48 months (G) after the end of intensity-modulated radiotherapy. Three dimensions of fatigue are assessed during follow-up: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Cancer-related fatigue has previously been reported as a side effect of PCa treatment in up to 80% of men [2730]. Few studies have investigated levels of fatigue in men who have exclusively undergone RARP for PCa; however, much work has been conducted in men receiving ADT and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-related fatigue has previously been reported as a side effect of PCa treatment in up to 80% of men [2730]. Few studies have investigated levels of fatigue in men who have exclusively undergone RARP for PCa; however, much work has been conducted in men receiving ADT and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that lower education level has been associated with obesity in the general population [25,26], more comorbidities in cancer patients in general [12], and higher fatigue level in PCa [27,28] as well as [29] breast cancer populations. We also recognize that previous research [30][31][32] has reported the opposite results on the relationship between education and fatigue levels in cancer patients, i.e., those with higher education having higher fatigue level. This discrepancy may be due F I G .…”
Section: Health-related Outcomesmentioning
confidence: 58%
“…If radiosensitivity is indeed implicated in development of RIF, an unusually sensitive or resistant prostate cancer response to radiotherapy may warn the treating oncologist of an increased risk of RIF by the patient. Because PCPs receiving intensity-modulated radiotherapy seem to experience the highest fatigue levels at end of radiotherapy and the ensuing three months, 111 an oncologist suspicious of RIF PCP may consider enrolling their patient in prophylactic RIF treatment before the end of radiotherapy series (i.e., the peak of expected fatigue). However, although these clinical implications are interesting and have utility, the definitive role of radiosensitivity in the development of RIF must be further investigated, as the herein provided evidence is suggestive at best.…”
Section: Interpreting the Results: Is Radiosensitivity Implicated In mentioning
confidence: 99%